PPAR-γ agonist rosiglitazone ameliorates peritoneal deterioration in peritoneal dialysis rats with LPS-induced peritonitis through up-regulation of AQP-1 and ZO-1. Issue 3 (21st June 2018) - Zhang, Yunfang; Feng, Junxia; Wang, Qi; Zhao, Shili; Xu, Jiaqi; Li, Hongyan
Abstract : Peritonitis is still a major cause of the death in peritoneal dialysis (PD) patients despite the significant decline of the peritonitis rates in recent years. The present study is designed to evaluate the therapeutic potential of peroxisome proliferator-activated receptor-γ agonist, rosiglitazone, on the structure and function of the peritoneum in a PD rat accompanied with peritonitis induced by lipopolysaccharide (LPS). Our data showed that the peritoneal membrane in the LPS-only group showed increased peritoneal thickness, vessel density, and hypercellularity compared with the PD-only group. Rosiglitazone administration significantly inhibited increase of the three indicators in PD rats with LPS treatment. In line with this, rosiglitazone improved function of the peritoneum in LPS-induced PD rats receiving rosiglitazone, which was reflected by decreased D/P urea and D/P albumin. Mechanistically, rosiglitazone-mediated improvements in the damaged structure and function of the peritoneum in PD rats with LPS treatment were associated with reduced inflammation and preserving mesothelial cell monolayer resulted from up-regulation of AQP-1 and ZO-1. Our findings thus suggest that peroxisome proliferator-activated receptor γ (PPAR-γ) activation might be a reasonable strategy to prevent and ameliorate peritoneal deterioration in PD patients, especially with peritonitis.